Optimization of flash extraction, separation of ginsenosides, identification by HPLC-FT-ICR-MS and determination of rare ginsenosides in mountain cultivated ginseng. Issue 72 (11th December 2020) - Xu, Lei; Xu, Jing; Shi, Guohui; Xiao, Shengnan; Dai, Rongke; Wu, Shao; Sun, Baoshan; Zhang, Xiaoshu; Zhao, Yuqing
Abstract : 23 ginsenosides, including rare ginsenosides, were separated from MCG by flash extraction technique. Through quantitative analysis, we found that the content of rare ginsenosides in MCG was higher than that in CG. Abstract : In this paper, we used the flash extraction method (FEM) to extract ginsenosides from mountain cultivated ginseng (MCG), optimized the FEM process by response surface methodology (RSM), and separated 23 kinds of ginsenosides from MCG, including rare ginsenoside Rg3, 20( R / S )-Rg2, Rk3, 20( S )-Rh2, 20( R )-Rh1, F1 and Rg6 . Among them, notoginsenoside R1 was isolated from MCG for the first time. Additionally, we established an HPLC-FT-ICR-MS method to accurately identify 20 ginsenosides in MCG, and quantitatively analyzed the differences in the content of rare ginsenosides in MCG and Garden-Cultivated Ginseng (CG) by HPLC-UV. The results showed that the chemical components of MCG and CG were similar, but the ginsenoside content of MCG was double that of CG. Notably, the content of ginsenoside 20 ( S )-Rh2 and 20 ( R )-Rh1 had the largest difference, and the content in MCG was 33 and 24 times higher than that in CG, respectively. Through quantitative analysis, we clarified the reason why the activity of MCG is stronger than that of CG, which provided a theoretical basis for clinical application and further research of MCG.